The Myth of Religious “Radicalism” - Amanah Nurish (Al-Albab, 2020)
This work examines an academic exposure on the issues of religious radicalism increasing globally not only in the West but also in the east countries. As a majority Muslim populated country, Indonesia is one of the reluctant examples in facing the problem of religious radicalism. In addition, this research paper examines the term of “radicalism” politically associated with extremism and terrorism. The primary issue is explicitly addressed to religious radicalism in terms of meaning and image. Hence, we perceive that religious radicalism can be understood as mainstream feature on religious behavior including religious actions leading to the steps of violent extremism or terrorism. Religious radicalism today is massively defined as a negative rather than positive connotation. Such glimpse traps us to be “narrow minded” in perceiving the role as well as the holy spirit of religions. Therefore, the critical questions of this research paper include what happens with the framing of religious radicalism today; How is the historical narration of radicalism; and is it a problem when someone being radical to practice and understand religions or beliefs. Lastly, how philosophical meanings of the word radicalism alone response such debate. However, the general terminology of religious radicalism has led significant social, political, and cultural impacts toward religious harmony and religious life particularly in Indonesian context.